2009
DOI: 10.1029/2008je003156
|View full text |Cite
|
Sign up to set email alerts
|

Venus Express bistatic radar: High‐elevation anomalous reflectivity

Abstract: [1] Magellan (MGN) bistatic radar observations in 1994 confirmed earlier Pioneer Venus reports of unusual Venus surface reflectivity and emissivity at elevations above 6054 km radius. They also revealed that the anomalous values of surface dielectric constant e near Cleopatra Patera included a large imaginary component (e % Ài 100) at 13 cm wavelength, consistent with a semiconducting surface material. The MGN observations were conducted using a linearly polarized wave, canted at 45°with respect to the plane o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This same study found that the linear polarization ratio, analogous to σ 0 HV / σ 0 HH , has a maximum of about 0.5. As with other regions of Venus above about 6053‐km planetary radius, Maxwell Montes has enhanced surface reflectivity, consistent with a real dielectric constant of 20 or more and a potentially very high imaginary component [e.g., Simpson et al , 2009]. From Section 3, we expect that echoes arising from the dihedral mechanism will exhibit a steady increase in CPR as the real dielectric constant rises.…”
Section: Discussionmentioning
confidence: 54%
“…This same study found that the linear polarization ratio, analogous to σ 0 HV / σ 0 HH , has a maximum of about 0.5. As with other regions of Venus above about 6053‐km planetary radius, Maxwell Montes has enhanced surface reflectivity, consistent with a real dielectric constant of 20 or more and a potentially very high imaginary component [e.g., Simpson et al , 2009]. From Section 3, we expect that echoes arising from the dihedral mechanism will exhibit a steady increase in CPR as the real dielectric constant rises.…”
Section: Discussionmentioning
confidence: 54%
“…Over the past decades, orbital BSR experiments have been used to assess the textural (and in some cases, dielectric) properties of the surfaces of terrestrial bodies such as Mercury 2 , Venus 3 , the Moon 4 6 , Mars 7 , 8 , Saturn’s moon Titan 9 , and now comet 67P/CG 10 . In contrast to most orbital BSR experiments, Dawn’s HGA beam intersected Vesta’s surface at grazing angles of incidence near 89° and in a microgravity environment with substantial variability in its gravity field 11 , leading to a low and variable orbital velocity and hence a more challenging detection of the Doppler-shifted surface echo (hereafter simply referred to as the “surface echo”).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these hints of unusual bulk composition, tesserae in northern latitudes such as Maxwell Montes and other mountain ranges around Ishtar Terra show an abrupt change in radar backscatterabove ~5 km elevation, they have very high backscatter (high reflectivity) and appear in SAR images as if they were covered with "snow" (Masursky et al, 1980;Pettengill et al, 1988;Garvin et al, 1985;Klose et al, 1992a;Pettengill et al, 1992;Simpson et al, 2009;Treiman et al, 2016). The cause and nature of this "snow," and the abrupt change in radar backscatter at a "snow line" in the northern highlands, have been debated vigorously.…”
Section: Introductionmentioning
confidence: 99%